2013
DOI: 10.1200/jco.2012.47.3520
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study Evaluating the Survival of Patients With Locally Advanced Cervical Cancer Undergoing Laparoscopic Para-Aortic Lymphadenectomy Before Chemoradiotherapy in the Era of Positron Emission Tomography Imaging

Abstract: To our knowledge, this is the largest series of patients reported undergoing such a strategy. We obtained the same survival rate for patients with PA nodal metastasis ≤ 5 mm and patients without PA lymph node involvement, suggesting that this strategy is highly efficient in such patients. Conversely, the survival of patients with PA nodal involvement greater than 5 mm remained poor, despite the absence of extrapelvic disease on PET-CT imaging in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 28 publications
7
138
1
5
Order By: Relevance
“…Among the patients with lymph node metastasis > 5mm and / or capsular involvement and / or fixed nodes, the overall survival rate at four years was greater than 30%, much lower than in previous groups but greater than the overall survival of patients in FIGO stage IVB (distant metastases) 34,40,41 . Other groups performing surgical staging prior to combined treatment corroborate these results, observing low morbidity, especially after reaching the procedure's learning curve 44 .…”
Section: Advanced Stages Advanced Stages Advanced Stages Advanced Stamentioning
confidence: 64%
See 2 more Smart Citations
“…Among the patients with lymph node metastasis > 5mm and / or capsular involvement and / or fixed nodes, the overall survival rate at four years was greater than 30%, much lower than in previous groups but greater than the overall survival of patients in FIGO stage IVB (distant metastases) 34,40,41 . Other groups performing surgical staging prior to combined treatment corroborate these results, observing low morbidity, especially after reaching the procedure's learning curve 44 .…”
Section: Advanced Stages Advanced Stages Advanced Stages Advanced Stamentioning
confidence: 64%
“…When comparing the survival of women with para-aortic lymph node metastasis <5mm in diameter undergoing surgery, it was observed that it was similar to women with negative para-aortic lymph nodes (70% in four years) 40,41 . Among the patients with lymph node metastasis > 5mm and / or capsular involvement and / or fixed nodes, the overall survival rate at four years was greater than 30%, much lower than in previous groups but greater than the overall survival of patients in FIGO stage IVB (distant metastases) 34,40,41 .…”
Section: Advanced Stages Advanced Stages Advanced Stages Advanced Stamentioning
confidence: 96%
See 1 more Smart Citation
“…В 2013 г. S. С. Gouy и со-авт. опубликовали результаты проспективного иссле-дования по сравнению данных совмещенной пози-тронно-эмиссионной и компьютерной томографии с результатами хирургического стадирования [12]. В исследование были включены 237 больных с IB2-IV стадией РШМ с клинически негативными лим-фатическими узлами.…”
Section: обзорные статьиunclassified
“…One study examined the efficacy of extending the radiation therapy (RT) field to the paraaortic region in patients with paraaortic lymph node involvement and showed therapeutic benefit especially in patients with small volume nodal disease [6] . A randomized controlled trial examining surgical versus radiology staging and treatment of paraaortic lymph node involvement is ongoing [7] .…”
Section: Introductionmentioning
confidence: 99%